PERFORMANCE OF COMMITMENT MAKING OFFICIALS - MUMU, APRILIA; POSUMAH, JOHNNY HANNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
PPK is an official who is authorized to make decisions and actions that result in the expenditure of the budget and is responsible for the implementation of the procurement of goods or services. The focus of this research is the performance of commitment-making officials at BPJN XV Manado in terms of quantity of work, quality of work, knowledge of work, creativity, cooperation, determination, initiative and personal quality. In this case it aims to find out how the performance of commitment-making officials in the ministry of public works and public housing BPJN XV Manado. The research method used is descriptive method with a qualitative approach. The instrument in this study is the researcher itself based on theoretical indicators according to Gomes expert. The indicator consists of quantity of work, quality of work, knowledge of work, creativity, cooperation, constancy, initiative, personal quality. The data analysis technique used in this study is an interactive technique according to moleong. The results of the study show that commitment-making officials have carried out their functions well, although there are still obstacles or problems faced. Suggestions that can be given need to be increased again the quantity of work ppk.Kata Kunci : the performance, commitment maker.PENDAHULUANDalam Perpres